The influence of acoustic nonlinearity on absorption properties of Helmholtz resonators. Part I. Theory - MEISSNER, M. (Archives of Acoustics, 1999)
This is the first of two companion papers concerned with the nonlinear absorption of Helmholtz resonators at a high amplitude incident wave. The phenomenon has been examined theoretically by use of a model of the acoustic field in the neighbourhood of the resonator placed at the end of cylindrical tube. The calculation results have shown that the peak of the absorption coefficient occurs when the nonlinear resistance is equal to the radiation resistance of the resonator. The full experimental investigations of this phenomenon and a comparison between theoretical and experimental data will be presented in the companion paper (Part II).